Diversity and Relative Abundance of Mosquito (Diptera: Culicidae) within Human Habitat in the District of Thane, Maharashtra, India - Kazi, Rozmina A.; Soni, Shouriehebal (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Mosquito’s form an integral part of our ecosystem. They act as vector in transmitting diseases and weakening the human immune system. A large amount of the country’s economy is expended in controlling the growth and spread of mosquitoes and the associated diseases. In the current study dead mosquitoes from different areas of Mira Bhayander Thane district were collected and identified using standard identification methods. The study was focused on the three genera Aedes, Anopheles and Culex as they are most commonly found in Mumbai and Thane region and are responsible for diseases like dengue, malaria, filariasis, etc which are currently on the rise. A total of 1123 dead mosquitoes were collected and it was observed that the population of Culex was highest and Anopheles was the least. Relative abundance of species was also calculated which concluded that the Aedes and Culex mosquitoes were the dominant genera whereas the Anopheles was the subdominant genera. The present study will aid in limiting the spread of diseases by controlling the growth of Culex and other mosquitoes.